Firm Characteristics, Board Structure and Corporate Social Responsibility Expenditure and Tax Avoidance in Ghana - Musah, Alhassan; Nukpe, Philip; Padi, Abigail; Amanor, Daniel Maunge Kweku (Indonesian Journal of Sustainability Accounting and Management, 2024)
The aim of this study is to examine the determinants of tax avoidance in Ghana, with a particular focus on firm characteristics, corporate governance, and corporate social responsibility (CSR) expenditure. The study employs quantitative methods, analysing ten years of data (2012-2021) extracted from the annual reports of listed firms. The results indicate that firm size, CSR expenditure, board independence, and foreign ownership are significant determinants of tax avoidance. In contrast, firm profit, gender diversity, and debt-to-equity ratio are found to be statistically insignificant. Notably, larger firms with higher profits and increased leverage tend to engage more in tax avoidance. The study also reveals a negative relationship between tax avoidance and both board independence and gender diversity, whereas foreign ownership and CSR expenditure are positively associated with tax avoidance. The study highlights the importance of CSR expenditure in understanding tax avoidance motives, suggesting that firms with significant CSR activities may require closer scrutiny by tax authorities to prevent aggressive tax practices. The value of this study lies in its inclusion of CSR expenditure as a novel factor influencing tax avoidance, providing fresh insights for researchers and policymakers on how firm characteristics and governance structures affect tax behaviour.